Seeing children's TV (SEECTV) the values presentation of the children's shows of ABS-CBN2, GMA7, and TV5 - Timoteo, Nicolle S. (2012)
"The study delved into the portrayal of the 10 values specified by the Department of Education in the children's shows of ABS-CBN2, GMA7, and TV5. The values portrayals of the said shows were considered as the network's public service in the context of the children's values formation. Anchored on Maletzke's model of communication, the Agenda-Setting Theory, the Cultivation Theory, and the Self-Determination Theory, this study looked into each element of the communication process, from the agenda-setting of the networks, to the audiences' reception of the values presentation of the children's shows. A grasp on the media agenda was gleaned from the context and textual analyses of selected children's programs from the three networks, and focus interviews with writers, producers, and director of these shows. Focus group discussions with children, parents, and teachers, on the other hand, reflected the children's reception of the program's values presentation. Generally, the locally produced and the foreign children's programs of the three networks portrayed values. Concern for others and politeness were the values most shown: while love of country and obedience were presented the least. Among the children's shows and analyzed, Batibot promoted the most number of values while Why Not presented the least. Among the networks, values presentation was most evident in TV5 and least observed in ABS-CBN2. Drawing from the perspectives of the networks and the audiences, it was found that entertainment and profit motives are married in the TV networks' communication with their child-audiences, as influenced by the industry's business nature and social responsibility. This was mirrored by the children's preference of TV programs, in terms of values-content and entertainment-value. Moreover, it was also established in this study that TV networks contribute to the children's values formation by producing children's programs that are both value-laden and entertaining."